Correlação entre 6-sulfatoximelatonina, distúrbios do sono e citocinas inflamatórias em Transtornos do Espectro do Autismo (TEA) - Fadini, Cintia Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
O Transtorno do espectro do autismo (TEA) é um conjunto de afecções do neurodesenvolvimento que comprometem principalmente a interação social, a comunicação e o comportamento. Na sintomatologia do TEA destaca-se a alta prevalência de distúrbios severos no ritmo sono-vigília. Uma das possíveis causas de problemas na qualidade do sono em crianças seria o padrão anormal da produção de melatonina, hormônio produzido pela glândula pineal, capaz de modular a qualidade do sono, graças à sua função como transdutora da informação fotoperiódica ambiental, além disso, esta molécula é controlada por moléculas que sinalizam inflamação. O presente estudo correlaciona o conteúdo do metabólito da melatonina, 6-Sulfatoximelatonina (aMT6s) à distúrbios do sono e às citocinas TNF e IL-6 em TEA. Participaram do estudo 36 indivíduos, de ambos os gêneros, idade entre 4-18 anos (média de 9,7 +/- 4,1), divididos em Grupo pesquisa (GP): 18 indivíduos com TEA e Grupo controle (GC): 18 indivíduos controles. Dentre os indivíduos do GP, quanto ao diagnóstico, 56% apresentaram autismo, 17% PDD-NOS (Transtorno Invasivo do Desenvolvimento Sem Outra Especificação) e 28% síndrome de Asperger. Para a caracterização dos distúrbios do sono e comportamento foi utilizada a Escala de Distúrbios...

The autism spectrum disorder (ASD) is a group of neurodevelopmental disorders that involve mainly social interaction, communication and behavior. On the symptomatology of ASD highlights the high prevalence of sleep-wake cycle disturbances. One of the causes of sleep disturbances in children is the abnormal pattern in the melatonin production by the pineal gland. This hormone can modulate the quality of sleep due to its function as transducing photoperiodic information from the environment. Besides being controlled by the photoperiodic information melatonin synthesis also is controlled by signaling molecules inflammation. The present study correlates sleep disorders with the contents of aMT6s, TNF and IL-6 in TEA. 36 individuals, of both genders, aged 4-18 years (mean 9.7 + / - 4.1), were analyzed being 18 individuals with ASD (research group - GP) and 18 control subjects (control group-GC). In the GP regarding the diagnosis, 56% had autism, 17% PDD-NOS (Pervasive Developmental Disorder Not Otherwise Specified) and 28% Asperger syndrome. For the sleep disorders and behavior characterization were used respectively the Escale of Sleep Disorders in Children (ESDC) and Child Behavior Checklist - CBCL. The measurements of aMT6s, TNF and IL-6 contents were performed on urine or saliva by ELISA. For data analysis we used descriptive statistics, Mann- Whitney U test for comparison between two groups and linear correlation coefficient of Spearman, the value of significance was 5%. The ESDC showed that 44% of GP individuals have at least one type of sleep disorder, and the GP has higher scores than the CG in the disorder of onset and sleep maintenance. Individuals of the GP had higher scores compared to the GC for total behavior problems, withdrawal problems, social problems, thought and attention problems... (Complete abstract click electronic access below)
Keywords: Autism spectrum disorder (ASD); Autismo; Melatonina; Disturbios do sono; Comportamento humano; Citocinas; Sistema nervoso central – Inflamação